2006
DOI: 10.1038/nsmb1134
|View full text |Cite
|
Sign up to set email alerts
|

Probing the activation-promoted structural rearrangements in preassembled receptor–G protein complexes

Abstract: Activation of heterotrimeric G proteins by their cognate seven transmembrane domain receptors is believed to involve conformational changes propagated from the receptor to the G proteins. However, the nature of these changes remains unknown. We monitored the conformational rearrangements at the interfaces between receptors and G proteins and between G protein subunits by measuring bioluminescence resonance energy transfer between probes inserted at multiple sites in receptor-G protein complexes. Using the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
462
3
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 405 publications
(516 citation statements)
references
References 46 publications
45
462
3
6
Order By: Relevance
“…1 A and B). A large body of experimental evidence (16,(21)(22)(23)(24)(25) supports the importance of the rearrangement of the GTPase and helical domains of Gα to create the necessary route for GDP dissociation. In particular, two flexible interdomain linkers appear to act together as a hinge during the opening of the helical domain away from the GTPase domain.…”
Section: Resultsmentioning
confidence: 99%
“…1 A and B). A large body of experimental evidence (16,(21)(22)(23)(24)(25) supports the importance of the rearrangement of the GTPase and helical domains of Gα to create the necessary route for GDP dissociation. In particular, two flexible interdomain linkers appear to act together as a hinge during the opening of the helical domain away from the GTPase domain.…”
Section: Resultsmentioning
confidence: 99%
“…that detects the agonist-promoted separation of Gα i1 and Gγ 2 in intact cells (Fig. 1A) (32). CXCL12 induces a rapid decrease in BRET signal between Gα i1 -91RLucII and GFP10-Gγ 2 in cells coexpressing the unmodified CXCR4 and Gβ 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that G-proteins exist in a stable complex with their cognate receptor [23,24], suggesting that receptor-effector coupling is mediated through dynamic conformational changes. In accord with this concept, a specific ligand-receptor interaction may mediate agonist activation of one effector pathway, yet act as antagonist for alternate pathway [25], a property likely to be modulated by dimerization.…”
Section: Discussionmentioning
confidence: 99%